Pemanfaatan Sistem Informasi Gampong (Sigap) dalam Meningkatkan Kualitas Pelayanan Publik di Gampong Ulee Tuy - Wilda, Raihan; Marliana; Rifaldi, Abid; Taufik (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Gampong Ulee Tuy is located in Darul Imarah District, Aceh Besar Regency. This village, which has natural resources, is still in the category of a developing village. This article focuses on discussing the use of SIGAP to improve the quality of public services in Gampong Ulee Tuy. The research method was carried out through observation and interviews with village officials. The results of the interviews were used to determine various points of view regarding SIGAP by Gampong Ulee Tuy officials. This research uses six (six) indicators, namely system quality, information quality, service quality, usage, user satisfaction, and net benefits. The research results show that SIGAP was welcomed by village officials because it would make it easier for them to collect data. Overall, all indicators were implemented well because the process of conveying information to the public was quickly accessible. However, it is necessary to immediately add correspondence templates to speed up public services for the community. The addition of new features also needs to be in accordance with the village's needs, and the latest version must be continuously updated so that the security of the data in SIGAP can be guaranteed.